The Effect of Red Sirih Leaf Drinking (Piper Crocatum) Towards Resin Violence Composites of Nanofiller in Laboratory of Makassar Working Center - Masriadi; Andy Fairuz Z, Eva; Sarahfin Aslan; Chusnul Chotimah; Nurasisa Lestari; Isma Pebrianti (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background. To determine the effect of soaking red betel leaves against the hardness of nanofillercomposite resins. Materials and Methods. The research applied True Experimental Laboratory methodwith one group pretest posttest. The 18 samples of nanofiller composite resin were obtained throughpurposive sampling. The samples were light cured then soaked in red betel leaf solution for 28 minutes.Then, the hardness measurements were performed using VickerHardness Tester. Results. The results ofpaired sample t-test indicated the effect of soaking red betel leaf (p 0.002 <0.05) and sterile aquadest (p0.026 <0.05) on the surface hardness of nanofiller composite resin. Conclusion. The effect of soakingred betel leaves on the surface hardness of nanofiller composite resin was obtained.